Peran Penanggung Jawab Program Sks Dalam Manajemen Kurikulum 2013 Berbasis Sistem Kredit Semester Di Mtsn 3 Nganjuk - Ira Nurjayanti (STAI AN-NAJAH INDONESIA MANDIRI, 2023)
In the education segment, Indonesia continues to strive to develop and improve the curriculum in order to achieve the educational goals of the Gold Generation. The 2013 curriculum is almost evenly applied to all levels of education units in Indonesia, some institutions apply it with certain systems such as the Semester Credit System (SKS). The general characteristic of the 2013 Curriculum is that educational goals focus on learning outcomes, while credits are a tactic to achieve these goals. Unfortunately, behind the luck of the SKS applied at MTsN 3 Nganjuk, there is a role in charge of the SKS Program which has not been much highlighted. This research is entitled